Transcriptional comparison of adult human primary Retinal Pigment Epithelium, human pluripotent stem cell-derived Retinal Pigment Epithelium, and ARPE19 cells - Markert, Elke K.; Klein, Holger; Viollet, Coralie; Rust, Werner; Strobel, Benjamin; Kauschke, Stefan G.; Makovoz, Bar; Neubauer, Heike; Bakker, Remko A.; Blenkinsop, Timothy A. (Frontiers in Cell and Developmental Biology, 2022)
The therapeutic potential of pluripotent stem cells is great as they promise to usher in a new era of medicine where cells or organs may be prescribed to replace dysfunctional tissue. At the forefront are efforts in the eye to develop this technology as it lends itself to in vivo monitoring and sophisticated non-invasive imaging modalities. In the retina, retinal pigment epithelium (RPE) is the most promising replacement cell as it has a single layer, is relatively simple to transplant, and is associated with several eye diseases. However, after transplantation, the cells may transform and cause complications. This transformation may be partially due to incomplete maturation. With the goal of learning how to mature RPE, we compared induced pluripotent stem cell-derived RPE (iPSC-RPE) cells with adult human primary RPE (ahRPE) cells and the immortalized human ARPE-19 line. We cultured ARPE-19, iPSC-RPE, and ahRPE cells for one month, and evaluated morphology, RPE marker staining, and transepithelial electrical resistance (TEER) as quality control indicators. We then isolated RNA for bulk RNA-sequencing and DNA for genotyping. We genotyped ahRPE lines for the top age-related macular degeneration (AMD) and proliferative vitreoretinopathy (PVR) risk allele polymorphisms. Transcriptome data verified that both adult and iPSC-RPE exhibit similar RPE gene expression signatures, significantly higher than ARPE-19. In addition, in iPSC-RPE, genes relating to stem cell maintenance, retina development, and muscle contraction were significantly upregulated compared to ahRPE. We compared ahRPE to iPSC-RPE in a model of epithelial-mesenchymal transition (EMT) and observed an increased sensitivity of iPSC-RPE to producing contractile aggregates in vitro which resembles incident reports upon transplantation. P38 inhibition was capable of inhibiting iPSC-RPE–derived aggregates. In summary, we find that the transcriptomic signature of iPSC-RPE conveys an immature RPE state which may be ameliorated by targeting “immature” gene regulatory networks.